2014
DOI: 10.1098/rsif.2014.0090
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling novel synergies between organometallic and biological partners: a quantum mechanics/molecular mechanics study of an artificial metalloenzyme

Abstract: In recent years, the design of artificial metalloenzymes obtained by the insertion of homogeneous catalysts into biological macromolecules has become a major field of research. These hybrids, and the corresponding X-ray structures of several of them, are offering opportunities to better understand the synergy between organometallic and biological subsystems. In this work, we investigate the resting state and activation process of a hybrid inspired by an oxidative haemoenzyme but presenting an unexpected reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Another aspect is the full relaxation of the first coordination sphere of the metal during the binding. Even if major changes of this environment are rarely observed in the structures of metallodrugs bound to their targets, this aspect could be studied, as demonstrated in the literature, , through QM/MM refinement.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect is the full relaxation of the first coordination sphere of the metal during the binding. Even if major changes of this environment are rarely observed in the structures of metallodrugs bound to their targets, this aspect could be studied, as demonstrated in the literature, , through QM/MM refinement.…”
Section: Discussionmentioning
confidence: 99%
“…The calculations showed that the unusual binding mode in the X-ray structure was linked to (1) the smaller size of salophen with respect to the natural substrate (the heme) and (2) the flexibility of the helix that contains the glutamate. Moreover, we could unambiguously associate the X-ray structure to an unprecedented resting state and identify the entire activation mechanism of the enzyme including cofactor–host induced motions …”
Section: Recompilation Of Arm Modeling Resultsmentioning
confidence: 99%
“…In particular, the possibility of multiple coordination and stabilization through secondary interactionshardly demonstrable with most of the experimental techniques (ESI-MS, CD, and UV–vis)can be substantiated by docking methods. A possible improvement of the bond distances and angles could be obtained through refinement of the metal binding sites predicted by docking through the quantum mechanics/molecular mechanics (QM/MM) method (see refs and ).…”
Section: Discussionmentioning
confidence: 99%
“…The background of the docking is thoroughly discussed in refs and and the historical development of the methods in refs . Initially, the method was applied to the inert binding of small organic molecules, and only subsequently were the first attempts to simulate the interaction of metal-containing ligands made (Scheme a). , However, like for most force field-based approaches, dealing with metallo ligands is far from straightforward because the effect of the metal and the possibility that one or more coordination bonds are formed must be considered. Even if covalent docking methods are available for software such as GOLD , Autodock , CovalentDock , and Docktite , their applications to metal complexes have several limitations: for example, the formation of chemical bonds is forced a priori through energetic restraints and is generally limited to specific bond classes.…”
Section: Introductionmentioning
confidence: 99%